Re-interpretation as transformation. Perspectives and challenges for Old Testament interpretation - D.J. Human (Acta Theologica)
This contribution explains that the re-interpretation of theological motifs or ideas leads to transforming theology and religion.  This phenomenon takes place within the corpus and boundaries of the Old Testament. Innerbiblical debate or “later” texts that re-interpret “earlier” texts underscore this process and confirm a transformed theology that is relevant and life-giving for the “new” or “later” context. Because these processes happened within the range of a long history of development of Old Testament literature, the article first discusses important hermeneutical realities or directives for Old Testament interpretation. It then mentions a few approaches to, and challenges of interpreting Old Testament literature. Finally, it briefly portrays how the book of Ruth re-interpreted certain pentateuchal texts as an act of transforming theology.